A dictionary of law / [Edited by] Jonathan Law - Law, Jonathanedited
This bestselling dictionary is an authoritative and comprehensive source of jargon-free legal information. It contains over 4800 entries that clearly define the major terms, concepts, processes and the organisation of the English legal system. Now in its ninth edition, it has been fully updated to incorporate recent case law and the latest legislation, such as the Modern Slavery Act 2015, the Brexit legislation and changes in consumer, tax and family law.